Dielectric Spectroscopy as a Condition Monitoring Technique for Low-Voltage Cables: Onsite Aging Assessment and Sensitivity Analyses - Simone Vincenzo Suraci; Chuanyang Li; Davide Fabiani (Energies, 2022)
This work presents the development, validation, and sensitivity analyses of a portable device capable of performing high-frequency dielectric spectroscopy tests on site. After a brief introduction on the operation principle and the description of the impact of frequency on dielectric spectroscopy, the article presents the results of tests on reference samples confirming good agreement with expected values. The frequency region in which the device operates, 1–200 kHz, was chosen because of its correlation with oxidative species of polymeric compound. The sensitivity analyses were performed measuring the dielectric response of low voltage cables with different aged lengths. The outcome of these tests is twofold. On the one hand, they confirm the suitability of the technique for aging evaluation, and, on the other hand, they allow the assessment of the minimum aged length (damage ratio) which causes appreciable variations on the obtained dielectric spectrum. This quantity was found to be ~35% of the total cable length.